Rare pathogenic nucleotide variants of mitochondrial DNA associated with Leber's hereditary optic neuropathy - Andreeva, N A; Murakhovskaya, Yu K; Krylova, T D; Tsygankova, P G; Sheremet, N L (Vestnik oftal'mologii, 2023)
Patients with Leber Hereditary Optic Neuropathy (LHON) in most cases have one of the three most common mutations: m.11778G>A in the gene, m.3460G>A in the gene, or m.14484T>C in the gene. According to the international Mitomap database, in addition to these three most common mutations, there are 16 other primary mutations that are even more rare. There are nucleotide substitutions that are classified as candidate or conditionally pathogenic mutations. Their involvement in the disease development is not proven due to insufficient research. Moreover, in many publications, the authors describe new primary and potential mitochondrial DNA mutations associated with LHON, which are not yet included in the genetic data bases. This makes it possible to expand the diagnostic spectrum during genetic testing in the future. The advancements in genetic diagnostic technologies allow confirmation of the clinical diagnosis of LHON. The importance of genetic verification of the disease is determined by the existing problem of differential diagnosis of hereditary optic neuropathies with optic neuropathies of a different origin.